A Spectrum of Ophthalmic Diseases in a Tertiary Care Hospital in Peshawar, KPK; a 10-Year Retrospective Study - Omer Nasim, Salman Khan, Muhammad Rafiq Afridi Khalid Saifullah Baig (Pakistan Journal of Ophthalmology, 2019)
Correspondence to: Omer Nasim Ophthalmology Unit Rehman Medical Institute (RMI), Peshawar Email: discover.omer@gmail.com Purpose: To assess the frequency of different eye morbidities in the patients presenting at a tertiary care Hospital in Peshawar. Study Design: Cross sectional study. Place and Duration of Study: Ophthalmology unit of Rehman Medical Institute (RMI), Peshawar from February 2004 to month of March 2014. Material & Methods: This research involved accessing the data bank kept by the Hospital. All ocular morbidities seen during the study period was included in the study while those who presented with the diseases of the eye due to some other systemic condition were excluded. Patients were categorized according to their gender and year of admission. The age categories were divided into 5 groups, 0-20, 21-40, 41-60, 61-80, 81-100 years’ category. The data collected was analyzed using MS Excel 2013. Results: A total of 1869 patients were examined out of which 49.92% were male and 50.07% were female. The ocular examination revealed that out of the 1869 patients, 57.30% of the patients suffered from Cataract, 4.86% patients suffered from Pterygium, 4.76% suffered from Strabismus, 1.65% patients suffered from Glaucoma and the remaining 31.43% suffered from various spectrum of diseases. Female preponderance was more than males in the sense of general morbidity of ocular disorders.